The portrayal of sex rôles in South African television advertisements - Alta Oberholzer; Gustav Puth; Jan Myburgh (Communicare)
The study comprised an analysis of the portrayal of sex rôles in South African television advertisements against the background of findings from similar studies in other societies. General results of these studies indicated a somewhat stereotyped and partly inferior social portrayal of women in advertising. The results of the present study indicated a similar pattern of female advertising roles to those found in studies of other societies. Women were predominantly depicted in a housewife/mother role, which is contrary to actual female contributions in the field of human resources.